ANALISIS EFISIENSI PADA CV. ZAKIAH DI SAMARINDA - Henri Fauli (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2022)
This research is motivated by the company's desire to continue to develop its business by looking at the company's ability to procure goods or sales and generate profits or profits by analyzing the company's efficiency ratio seen from the balance sheet and income statement. The problem that is formulated is what causes an increase in inventory efficiency in 2020 compared to 2019. The hypothesis proposed is that it is suspected that sales caused an increase in inventory efficiency in 2020 compared to 2019. The analytical tool used is the efficiency ratio analysis method or activity ratio which includes the total assets turnover, fixed assets turnover, inventory turnover, receivable turnover, and net working capital turnover, in order to solve problems and efforts to answer the proposed hypothesis. Based on the results of the analysis that has been carried out, it can be concluded that the efficiency ratio consisting of Total Assets Turnover in 2019 rotated 7.18 times, increasing by 0.5 times its turnover in 2020 to 7.68 times. Likewise, Fixed Assets Turnover in 2019 rotated 33.8 times, increasing by 2.7 times in 2020 to 36.5 times. Receivable Turover in 2019 rotated 28.3 times, increasing by 1.6 times in 2020 to 29.9 times. Meanwhile, Inventory Turnover in 2019 rotated 913.8 times, increasing by 14.8 times in 2020 to 928.6 times its turnover. Sales made by the company also experienced an increase from 2019 to 2020, namely Rp. 80,576,014.00 in 2019 increased by Rp. 14,875,50,00 to Rp. 95,415,514.00 in 2020 and led to an increase in the company's inventory efficiency in 2020 compared to 2019 which was Rp. 1,112,750.00 in 2013 and Rp. 545,250.00 in 2019. The conclusion of this study is the efficiency ratio of CV. Zakiah in Samarinda for the period 2019 to 2020 has increased.